Values-Based Management of Archaeological Resources at a Landscape Scale. Issue 2 (May 2016) - McManamon, Francis P.; Doershuk, John; Lipe, William D.; McCulloch, Tom; Polglase, Christopher; Schlanger, Sarah; Sebastian, Lynne; Sullivan, Lynne
Abstract: Public agencies at all levels of government and other organizations that manage archaeological resources often face the problem of many undertakings that collectively impact large numbers of individually significant archaeological resources. Such situations arise when an agency is managing a large area, such as a national forest, land management district, park unit, wildlife refuge, or military installation. These situations also may arise in regard to large-scale development projects, such as energy developments, highways, reservoirs, transmission lines, and other major infrastructure projects that cover substantial areas. Over time, the accumulation of impacts from small-scale projects to individual archaeological resources may degrade landscape or regional-scale cultural phenomena. Typically, these impacts are mitigated at the site level without regard to how the impacts to individual resources affect the broader population of resources. Actions to mitigate impacts rarely are designed to do more than avoid resources or ensure some level of data recovery at single sites. Such mitigation activities are incapable of addressing research question at a landscape or regional scale.